Rancang Bangun Aplikasi Pembelajaran Sandi Pramuka Pada Siswa Tingkat Sekolah Dasar Berbasis Android - Hidayatullah, Hidayatullah; Sunarto, M. J. Dewiyani; Sutanto, Teguh (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2013)
Abstract: Scout Movement is a non-governmental agencies, which seeks to help the government and the community, in the community and nation building, especially in the field of education. One of the important activities of the scout is to memorize codes or commonly known by the code name. This time to learn the password scouts still use regular tutorial guide book as a paperback book and Skills General Terms books (SKU) causing lazy Elementary School students learn the password because scouts tend to get bored. To overcome this, the rapid development of technology by utilizing smartphones in independent learning, and multimedia facilities that can remove images, audio and animation, then the password scout learning application created as an application that can be used to perform the learning process in memorizing passwords scout syringe morse key feature and slideshow images semaphore. Learning application scouts password has been tested to 10 users with an average value of the application user satisfaction of 3.14 which indicates that the application of user interest is good. This application can be run on android 2.3.7 and minimal static, where the data does not change according to the provisions scout international Morse code and semaphore signals. Keywords: Android, Scouting, Learning